Penerapan Sistem Pengendalian Internal Tentang Persediaan Barang Dagang Pada PT Pinus Merah Abadi - Ni Made Yuni Ari Susanti; I Wayan Sudiana; I Made Endra Lesmana Putra (Hita Akuntansi dan Keuangan, 2026)
Through this research, we aim to delve into how internal control system for merchandise inventory is applied at PT Pinus Merah Abadi. Using a qualitative approach, data for the research were gathered via comprehensive interviews conducted with three primary sources who are directly engaged in inventory management. Analysis revealed that, by and large, the internal control mechanisms are functioning properly, supported by a sound control environment, skilled personnel, and well-defined standard operating procedures (SOPs). Nevertheless, the study also highlights certain weaknesses, particularly the absence of proper segregation of duties in inventory-related tasks, which may open the door to potential fraud. Additionally, issues related to handling damaged goods and recording errors (human error) still occur and can hinder the system's effectiveness. Communication regarding damaged goods is also not yet optimal. Nevertheless, the company has demonstrated a strong ability to assess risks and implement control activities that align with its established procedures.